2009
DOI: 10.1080/10550490902925540
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and Retention in Outpatient Alcoholism Treatment for Women

Abstract: Reviews of the dropout literature note significant attrition from addiction treatment. However, consistent predictors have not been identified and few studies have examined factors related to retention and engagement for women in gender-specific treatment. The current study consisted of 102 women and their partners randomized to individual or couples outpatient alcoholism treatment. Women attended more treatment sessions if they were assigned to individual treatment, older, had fewer symptoms of alcohol depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 64 publications
4
56
0
1
Order By: Relevance
“…We assumed that relationship satisfaction played an important role for utilization, which was supported by prior findings for men [10] and women [11]. Nevertheless, our results do not support this assumption.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…We assumed that relationship satisfaction played an important role for utilization, which was supported by prior findings for men [10] and women [11]. Nevertheless, our results do not support this assumption.…”
Section: Discussionsupporting
confidence: 49%
“…In prior studies in outpatient settings, age was not a significant predictor for the utilization [8, 10, 11]. A possible explanation for this difference could be the pre-selection of our BCT-sample: all individuals had already decided upon (an individual) inpatient treatment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There is some evidence that the following client-centered factors are related to early discontinuation of treatment: young and single patients, high severity of substance use, and lack of family stability. With regard to treatment-centered factors, positive therapeutic alliance, good clinician experience, and proactive participation of family members have been associated with lower attrition rates [32]. On the other hand, studies have shown mixed results with regard to depression symptoms [33].…”
Section: Discussionmentioning
confidence: 99%